2022
DOI: 10.3389/fmed.2022.839954
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Paget Disease With Melanocytic Proliferation Mimicking Malignant Melanoma in situ: A Case Report

Abstract: Several cases of pigmented mammary Paget’s disease (PMPD) mimicking cutaneous malignant melanoma have been reported. In these cases, the tumor cells are colonized by melanocytes, particularly with the presence of a population of melanocytes staining for HMB-45 and S100. Here, we report a case of mammary Paget disease (MPD) which was misdiagnosed as melanoma in situ due to the interpretation of the staining of melanocytic markers S-100, Melan-A, and HMB-45. The tumor cells strongly expressed CK7 and GATA3, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This case demonstrates a rare example of a CD30+ lymphoproliferative disorder masquerading as an atypical melanocytic proliferation, both clinically and histopathologically. There are a small number of non‐melanocytic tumors that can mimic melanoma in situ on histopathologic grounds, including pigmented squamous cell carcinoma in situ (Bowen disease) and extramammary Paget disease 4–6 . However, the differential diagnosis for pigmented neoplasms and epidermotropic CD30+ T‐cells rarely overlap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case demonstrates a rare example of a CD30+ lymphoproliferative disorder masquerading as an atypical melanocytic proliferation, both clinically and histopathologically. There are a small number of non‐melanocytic tumors that can mimic melanoma in situ on histopathologic grounds, including pigmented squamous cell carcinoma in situ (Bowen disease) and extramammary Paget disease 4–6 . However, the differential diagnosis for pigmented neoplasms and epidermotropic CD30+ T‐cells rarely overlap.…”
Section: Discussionmentioning
confidence: 99%
“…There are a small number of non-melanocytic tumors that can mimic melanoma in situ on histopathologic grounds, including pigmented squamous cell carcinoma in situ (Bowen disease) and extramammary Paget disease. [4][5][6] However, the differential diagnosis for pigmented neoplasms and epidermotropic CD30+ T-cells rarely overlap. The latter generally includes ALCL, lymphomatoid papulosis (LyP) type B, mycosis fungoides, and other cutaneous T-cell lymphomas, including primary cutaneous aggressive epidermotropic cytotoxic T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a similar case was stained with dual-labeling (PHH3 and Melan-A) and showed negative PHH3 labeling for the melanocytes, which indicated that the melanocytes were not undergoing mitosis. 18 Things may get even more complicated in the case of pigmented triple-negative breast cancers, as SOX10 also labels primary breast carcinomas, particularly those with the basal-like, triple-negative phenotype. [19][20][21] In this particular circumstance, it is imperative to meticulously evaluate suitable immunohistochemical stains.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic melanocytes are seen admixed within neoplastic cells, adding to the confusion, but can be identified using SOX10 and S100. Recently, a similar case was stained with dual‐labeling (PHH3 and Melan‐A) and showed negative PHH3 labeling for the melanocytes, which indicated that the melanocytes were not undergoing mitosis 18 . Things may get even more complicated in the case of pigmented triple‐negative breast cancers, as SOX10 also labels primary breast carcinomas, particularly those with the basal‐like, triple‐negative phenotype 19–21 .…”
Section: Discussionmentioning
confidence: 99%
“…As it was stated by Rao et al, the combined presence of neoplastic ductal cells and atypical melanocytes in a unique sample might occur due to the existence of a single mammary tumor of breast origin, undergoing bidirectional dedifferentiation [ 23 ]. Furthermore, the melanocytic population objectified in the epidermal layer was one of the prominent elements that raised the differential diagnosis challenge.…”
Section: Discussionmentioning
confidence: 99%